Evaluasi Usability pada Aplikasi Go-Jek Dengan Menggunakan Metode Pengujian Usability - Muhammad Ismail Farouqi; Ismiarta Aknuranda; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Gojek Indonesia (GO-JEK) is one of the companies that created taxibike online application in Indonesia. GO-JEK applications are growing rapidly so that has been downloaded more than 10 million times. Although it has been downloaded more than 10 million times but there are still some users who complain about the application of GO-JEK. From some user feedback, the GO-JEK app still has a problem in its users. These problems are part of the usability problem that existed in GO-JEK applications. Therefore, we need a more comprehensive problem digging in order to deepen the problems that occur to users of the application GO-JEK. Please also note how far the level of usability in the application GO-JEK. The usability level needs to be known to explain the usability of the GO-JEK app already at what level from the user side. This study provides evaluation results to determine the usability problems and usability levels that exist in the GO-JEK application using usability testing method. The results obtained from this study indicate that there are five usability problems that exist in the GO-JEK application. In addition, the usability level which consists of the level of convenience is 100%. the speed rate is of 0.01 goals / sec. the error rate is 0.1 and the satisfaction rate is 60% - 70%.